Scientific Thinking in Islamic Thought: Concept and its Importance - Alias Azhar (UIN Sunan Gunung Djati Bandung, 2017)
God’s revelations, as the main source of knowledge, do not deny, in any way our brain’s functional capabilities. The Quran acknowledges the necessity and importance of the brain. Islamic epistemology regards the brain as the second source of knowledge after the revelations. The holistic perspective on knowledge that is gained by mankind is that it is constructed by man in the context of their thinking culture, education and social concepts. Therefore, in this regard, thinking method directly relates to the objectives of Islam and its Sharia, and gives a significant implication towards understanding and developing Sharia as a dynamic knowledge area. This study combines three (3) methods, content analysis; historical method and comparison of the review of the history of the construction of Islamic thought and the review of screening methods Sociology Society background. The discussion this article covers the definition and concept of scientific thinking skills and scientific Islamic thought and the approaches of critical thinking in Islamic scientific thought. In reality, Muslims are not prohibited by their religion to think scientifically through scientific thinking methods, provided that it does not contradict with Islam. Some knowledge which is built through scientific thinking can be used to understand the Quranic texts more profoundly. Also, undeniably, the eminence of God’s revelations has been made evident and exploited to proof the existence of Allah.